Dumbbell configuration of silicon adatom defects on silicene nanoribbons - Huynh Anh Huy (Nature Portfolio, 2021)
Abstract Using density functional theory (DFT), we performed theoretical investigation on structural, energetic, electronic, and magnetic properties of pure armchair silicene nanoribbons with edges terminated with hydrogen atoms (ASiNRs:H), and the absorptions of silicon (Si) atom(s) on the top of ASiNRs:H. The calculated results show that Si atoms prefer to adsorb on the top site of ASiNRs:H and form the single- and/or di-adatom defects depending on the numbers. Si absorption defect(s) change electronic and magnetic properties of ASiNRs:H. Depending on the adsorption site the band gap of ASiNRs:H can be larger or smaller. The largest band gap of 1 Si atom adsorption is 0.64 eV at site 3, the adsorption of 2 Si atoms has the largest band gap of 0.44 eV at site 1-D, while the adsorption at sites5 and 1-E turn into metallic. The formation energies of Si adsorption show that adatom defects in ASiNRs:H are more preferable than pure ASiNRs:H with silicon atom(s). 1 Si adsorption prefers to be added on the top site of a Si atom and form a single-adatom defect, while Si di-adatom defect has lower formation energy than the single-adatom and the most energetically favorable adsorption is at site 1-F. Si adsorption atoms break spin-degeneracy of ASiNRs:H lead to di-adatom defect at site 1-G has the highest spin moment. Our results suggest new ways to engineer the band gap and magnetic properties silicene materials.